Salt Lake City Paper - Flotation Mechanism, A Discussion of the Functions of Flotation Reagents (with Discussion) - A. M. Gaudin (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
A great number of hypotheses has been advanced to explain the complex phenomena that are encountered in flotation. In the days of bulk-oil flotation, when a large quantity of oil was employed, it was observed that the oil-mineral aggregate floated above the ore-pulp because of its lesser density. With the advent of froth-flotation this phase of the theory had to be modified to take into account the presence of air bubbles. The reason why the mineral-bearing froth of today rises to the top of flotation cells is, of course, because the air-mineral aggregate, with whatever reagent may be associated with it, is lighter than the pulp. In an attempt to explain froth-flotation the fact has been emphasized that certain minerals are wetted and therefore remain in water; while others are not wetted and therefore become associated in preference with air. Such an "explanation" does not explain facts, it merely states them; for instance, it does not explain why minerals are wetted under some circumstances and not wetted under others. Going somewhat further, the wetting or nonwetting of minerals by water has been ascribed' to differences in the angles of contact between oil droplets and mineral surface at the surface of the minerals. This explanation, however, was abandoned when soluble flotation reagents came to replace the so-called "insoluble" reagents. Another theory, sponsored about 10 years ago by Ralston,² involves the effects of electric charges at the surface of the mineral particles and air bubbles. This theory, unfortunately, was not developed as fully as it seems desirable. The belief that adsorption phenomena might play a preponderant role in flotation3 has been rather widespread for the last 10 years. Unfor-